Keberlanjutan Mata Pencaharian melalui Pola Kemitraan: Analisis Break-Even Point dan Profitabilitas Peternakan Ayam Broiler di Sikaf Farm - Rizky Azura; Nuri Aslami; Muhammad Ikhsan Harahap (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study examines the profitability and break-even point of a broiler farming enterprise operating under a partnership model at Sikaf Farm, Manik Hataran Village, Simalungun Regency. Adopting a quantitative approach, the research is based on primary data collected through observation, interviews, and field notes. The analysis employed break-even point (BEP) and profitability assessment techniques. The findings indicate that Sikaf Farm exceeded the break-even threshold, with a minimum production requirement of 1,415 kg and a minimum price of 4,311.06/kg, while actual production reached 89,408 kg. Despite this, profitability measures reveal that the enterprise remains financially suboptimal, reflected in a revenue-cost (R/C) ratio of 0.81 and a profit margin of only 3.03%. These figures suggest that profits are still relatively low and that the business may experience losses during certain production cycles. High broiler mortality rates and inefficiencies in operational cost management constitute the principal challenges. To improve profitability and ensure the sustainability of the partnership model, it is crucial to enhance technical management practices, increase cost efficiency in housing systems, and strengthen collaboration with the core company